STUDI ANALISIS KEMAMPUAN PENYEDIAAN SUPLAI DAYA AKIBAT PENINGKATAN BEBAN DI GARDU INDUK NUSA DUA - Nur Ayu Puspita Indra Pratiwi; I Gede Dyana Arjana; Antonius Ibi Weking (Jurnal SPEKTRUM, 2018)
The area of South Bali is a tourist attraction that has many hotel buildings, villas, and tourism sector as well as a venue for the implementation of National and International events. Causing the burden on the Nusa Dua Main Entity will increase. Along with the load development, Nusa Dua Substation must be able to supply from GIS Airport and GIS Pesanggaran. Forecast load using linear regression to obtain the value of the development of the transformer load and power supply up to 5 years.The calculation of the growth rate of the transformer load of the Nusa Dua Substation Transformer is 8.9% per year, and the calculation of 2018 in Transformer 1 is 113.38A Trans-former 2 about 124.3A, and the Transformer 3 is 137.09A. The calculation results of the growth rate of power supply through the transmission of 150 Kv to the Nusa Dua Substation is 179,612A supplied from GIS airport, and 238.32A from GIS Pesanggaran. The difference between load and power supply in 2018 is 18.53A (0.430%) of GIS Airport and 24.53A (0.570%) of GIS Pesanggaran. Transformer 3 in 2025 is not capable of carrying the load, Transformer 2 can not loads in 2026, and Transformer 1 is not able to the burden in 2027. So that required the addition of new Transformer or construction of new substation in the area of increasing load.Keywords: growth rate, power supply, transformer.